2000
DOI: 10.1176/appi.ajp.157.6.1006
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Activation in Depression and Effects of Sertraline Treatment: An Open-Label Study

Abstract: Sertraline diminished the increased platelet secretion found among depressed patients, although the findings are limited by a lack of a placebo control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
0
3

Year Published

2001
2001
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(97 citation statements)
references
References 11 publications
5
89
0
3
Order By: Relevance
“…38 Interestingly, collageninduced platelet secretion, an integral component of the clotting cascade, is significantly reduced after treatment with sertraline. 39 The present data are in agreement with earlier in vitro observations, 14 suggesting that long-term therapy with sertraline is associated with inhibition of platelets and possibly other steps in the clotting cascade. Indeed, at 6 weeks after randomization, patients treated with sertraline exhibited a significant decrease in ␤TG, the well-defined platelet ␣-granule constituent.…”
Section: Discussionsupporting
confidence: 93%
“…38 Interestingly, collageninduced platelet secretion, an integral component of the clotting cascade, is significantly reduced after treatment with sertraline. 39 The present data are in agreement with earlier in vitro observations, 14 suggesting that long-term therapy with sertraline is associated with inhibition of platelets and possibly other steps in the clotting cascade. Indeed, at 6 weeks after randomization, patients treated with sertraline exhibited a significant decrease in ␤TG, the well-defined platelet ␣-granule constituent.…”
Section: Discussionsupporting
confidence: 93%
“…4,8,9 This was the a priori hypothesis of our study. SSRIs inhibit serotonin uptake into platelets, 11,26,27 block intracellular calcium mobilization, 28 and are associated with an increase in bleeding time.…”
Section: Depression Ssris and Platelet Functionmentioning
confidence: 82%
“…9,22 This may be attributable to the upregulation of platelet imidazoline 23 and serotonin 24 receptors and enhanced intraplatelet calcium mobilization 25 seen in patients with depression.…”
Section: Depression Ssris and Platelet Functionmentioning
confidence: 99%
“…Although in the middle of the nineties Alderman et al (1992) and Berk et al (1995) failed to find a modification in platelet aggregation or haemostasis in patients treated with SSRIs, the application of most modern techniques to measure platelet function led to the confirmation that SSRIs impair both the platelet secretory response (Markovitz et al 2000) and the platelet aggregation induced by ADP, collagen and thrombin (Serebruany et al 2001), and that they cause an inhibition of platelet plug formation as reflected by a significant prolongation of the closure-time measured with a platelet function analyzer (Hergovich et al 2000). Furthermore, in vitro studies have shown that addition of ADP to normal platelets in the presence of SSRIs causes microaggregation and primary aggregation but no or very little dense granule release which leads to the formation of loose and disaggregating clots (Maurer-Spurej 2005).…”
Section: Pharmacology Of Ssris On Platelets and The Biological Plausimentioning
confidence: 99%